Drug utilization study of some antibiotic in indoor setting at tertiary care teaching hospital in Central India: a descriptive study - Randad, Rahul D.; Bhagwate, Sudharam T.; Inamdar, Mohd. Khalid (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Antibiotics are one of the most important discoveries in the field of medicine and are widely used in reducing the infections. Irrational antibiotic use may result in increased cost of treatment, drug-drug interactions also cause severe adverse reactions. The objective of the study was to determine average number of antibiotics prescribed per prescription, to identify the indication for which antibiotics were commonly used and to determine the most commonly prescribed antibiotics in a tertiary care hospital. Methods: This was a retrospective observational study. About 300 patients who were prescribed antibiotics were included in the study. The data on antibiotic containing prescriptions from each patient was collected from the inpatient of medicine department. The study was carried out from August 2013 to July 2014. Results: Total 300 prescriptions studied, of which 195 (65%) prescriptions had 2 antibiotics per prescriptions and 105 (35%) prescriptions had more than 2 antibiotics per prescription. It was observed that out of 300 patients, 165 were male (55%) and 135 were female (45%). Fluoroquinolones were most commonly prescribed antibiotics and ciprofloxacin was prescribed mostly. Most of the prescriptions contained polypharmacy. The antibiotics treatment regimens given in most of the patients were without done culture sensitivity test before prescribing, which lead to irrational prescribing. Conclusions: Compliance to adopted treatment guidelines is still a major challenge hence there is an urgent need for following antimicrobial policy.